2019
DOI: 10.1186/s11671-018-2827-4
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of InGaAs/InAlAs Single-Photon Avalanche Photodiodes

Abstract: Theoretical analysis and two-dimensional simulation of InGaAs/InAlAs avalanche photodiodes (APDs) and single-photon APDs (SPADs) are reported. The electric-field distribution and tunneling effect of InGaAs/InAlAs APDs and SPADs are studied. When the InGaAs/InAlAs SPADs are operated under the Geiger mode, the electric field increases linearly in the absorption layer and deviate down from its linear relations in the multiplication layer. Considering the tunneling threshold electric field in multiplication layer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To further study and demonstrate the obtained results, in this part, we perform numerical calculations for the timeresolved intensity of absorption in In 0.53 Ga 0.47 As/In 0.52 Al 0.48 As prolate ellipsoidal QDs. We utilize those parameters for the calculation: the effective mass of the electron and the hole in the dot material In 0.53 Ga 0.47 As is m e = 0:042m 0 and m h = 0:052m 0 ; the bandgap of the dot material is E g = 750 meV [37,40]; the linewidth and the amplitude of pump laser are Γ = 0:1 meV and A p = 4 × 10 4 V/cm, respectively; the lifetime of excitons is chosen as T 1 = 40 ps; and the coherent time T 2 is assumed to be less than the lifetime T 1 as discussed above and is chosen as T 2 = 20 ps.…”
Section: Resultsmentioning
confidence: 99%
“…To further study and demonstrate the obtained results, in this part, we perform numerical calculations for the timeresolved intensity of absorption in In 0.53 Ga 0.47 As/In 0.52 Al 0.48 As prolate ellipsoidal QDs. We utilize those parameters for the calculation: the effective mass of the electron and the hole in the dot material In 0.53 Ga 0.47 As is m e = 0:042m 0 and m h = 0:052m 0 ; the bandgap of the dot material is E g = 750 meV [37,40]; the linewidth and the amplitude of pump laser are Γ = 0:1 meV and A p = 4 × 10 4 V/cm, respectively; the lifetime of excitons is chosen as T 1 = 40 ps; and the coherent time T 2 is assumed to be less than the lifetime T 1 as discussed above and is chosen as T 2 = 20 ps.…”
Section: Resultsmentioning
confidence: 99%
“…The PNR experiments has been frequently demonstrated by using InP-based SPADs. However, it has been reported that InAlAs-based SPADs can improve performance in terms of breakdown and temperature characteristics [24]. The higher avalanche breakdown probability in InAlAs potentially results in a higher single photon detection efficiency (SPDE) at a lower electric field when compared to InP-based SPADs [25].…”
Section: Introductionmentioning
confidence: 99%
“…The PNR experiments has been frequently demonstrated by using InP-based SPADs. However, it has been reported that InAlAs-based SPADs can improve performance in terms of breakdown and temperature characteristics [24]. The higher avalanche breakdown probability in InAlAs potentially results in a higher single photon detection efficiency (SPDE) at a lower electric field when compared to InP-based SPADs [25].…”
Section: Introductionmentioning
confidence: 99%